Mapping Early Pleistocene environments and the availability of plant food as a potential driver of early Homo presence in the Guadix-Baza Basin (Spain). Issue 155 (June 2021) - Altolaguirre, Yul; Schulz, Meike; Gibert, Luis; Bruch, Angela A.
Abstract: The Guadix-Baza Basin, in SE Spain, harbors hominin fossils and lithic artifacts dated to ca. 1.4–1.3 Ma, representing the first hominin habitat in the Iberian Peninsula and possibly in Western Europe. Recent palynological studies have described a high diversity of plant taxa and biomes existing in the basin at the time of hominin presence. However, the relationship between these hominins and their environment has not been fully explored. Two novel methodologies are developed. The first method maps the distribution of the Early Pleistocene vegetation units based on paleobotanical and paleogeographic data. The second method assesses the availability of edible plant parts using a combination of Early Pleistocene and modern taxa lists. The resulting vegetation maps reveal a great diversity of vegetation types. During dry (glacial) periods, the vegetation of the basin was represented mostly by steppes, with the appearance of forested vegetation only in the mountainous regions. During humid (interglacial) periods, Mediterranean woodlands represented the dominant vegetation, accompanied by deciduous and conifer forests in the areas of higher altitude. The lake system present in the basin also allowed for the presence of marshland vegetation. The assessment of the availability of edible plant parts reveals that early Homo could have found a high number of resources in marshland and riparian environments throughout the year. Mediterranean woodlands and deciduous forests also provided numerous edible plant parts. During dry periods, the availability of plant resources decreased heavily, but the prevalence of marshland and riparian vegetation and of forested vegetation in the areas of higher altitude could have sustained hominin communities during harsher climatic periods. However, the disappearance of the lake system and an increase of aridity after the Mid-Pleistocene Transition and during the Middle Pleistocene probably led to an impoverishment of plant resources available to early Homo in the Guadix-Baza Basin. Highlights: Maps for glacial and interglacial periods show great vegetation diversity. Earliest Homo in the Iberian Peninsula had access to multiple sources of plant food. Riparian and marshland vegetation were an important source of food during glacials. During Early Pleistocene, the basin could have acted as a glacial refugium for Homo. The loss of marshlands in the Middle Pleistocene may have affected hominins.